Genetic diversity in the natural populations of Pinus dalatensis Ferré (Pinaceae) assessed by SSR markers - Phong, Dinh Thi; Thu Hien, Vu Thi; Lieu, Tran Thi; Hiep, Nguyen Tien (Vietnam Journal of Science and Technology, 2016)
Pinus dalatensis Ferre’(Family: Pinaceae) is an endemic plant with restricted habitats at higher altitudes in Vietnam highland. The species are now near threatened by over-exploitation and habitat destruction. The genetic variation within and among populations of P. dalatensis was investigated by 41 microsatellite (single sequence repeat, SSR) primers, but only 11 SSR primers showed polymorphism bands. In all, 70 sampled trees from six populations in Vietnam highland were analyzed in this study, samples were collected from populations located in different altitude. A total of 40 allelic variants have been detected. The mean number of alleles per locus was 2.197. The SSR data showed a genetic diversity parameters within populations with an average of I = 0.524, Ho = 0.222, He = 0.317, Fis =0.333 and Ap = 0.106. The number private alleles (Ap) was only found in four populations, the Hoa Son population showed the highest (0.273), followed by Da Chay (0.182), and value of 0.091 for all Ngoc Linh and A Yun. Analysis of molecular variance analysis showed that most genetic variation was within populations of 57.504 % and among population of 42.496 %. The population pairwise differentiations indicated that most of the populations were significantly differentiated p < 0.001 with Fst values ranged from 0.195 to 0.418. This study highlights the importance of conserving the genetic resources of P. dalatensis species